2003
DOI: 10.1002/mus.10549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of static stretch training on neural and mechanical properties of the human plantar‐flexor muscles

Abstract: To determine the contributions of neural and mechanical mechanisms to the limits in the range of motion (ROM) about a joint, we studied the effects of 30 sessions of static stretch training on the characteristics of the plantar-flexor muscles in 12 subjects. Changes in the maximal ankle dorsiflexion and the torque produced during passive stretching at various ankle angles, as well as maximal voluntary contraction (MVC) and electrically induced contractions, were recorded after 10, 20, and 30 sessions, and 1 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
149
2
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(168 citation statements)
references
References 36 publications
13
149
2
4
Order By: Relevance
“…33,34 In the clinical setting, these two passive mechanical properties of muscles are best reflected by torque-angle curves. [10][11][12][13][14][15][16][17] Although more than one soft tissue structure spans a joint, the torque-angle curve of a joint can be used to primarily reflect the passive mechanical properties of an overlying multiarticular muscle (such as FPL muscle) when this muscle primarily restricts joint movement. Therefore, provided the FPL muscle is placed at a stretch by positioning the wrist, MCP and IP joints in full extension, the torque-angle curve of the CMC joint will primarily reflect the passive mechanical properties of the FPL muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 In the clinical setting, these two passive mechanical properties of muscles are best reflected by torque-angle curves. [10][11][12][13][14][15][16][17] Although more than one soft tissue structure spans a joint, the torque-angle curve of a joint can be used to primarily reflect the passive mechanical properties of an overlying multiarticular muscle (such as FPL muscle) when this muscle primarily restricts joint movement. Therefore, provided the FPL muscle is placed at a stretch by positioning the wrist, MCP and IP joints in full extension, the torque-angle curve of the CMC joint will primarily reflect the passive mechanical properties of the FPL muscle.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Clinical assessment tools have been designed using these principles to measure the extensibility of muscles such as the plantarflexor muscles, [18][19][20] hamstring muscles, 21,22 and extrinsic finger flexor muscles. 23 However, no equivalent device to measure the extensibility of the FPL muscle has been described.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, there are three main mechanisms used to explain an increase in muscle length: sarcomerogenesis [24,25], increase in stretching tolerance (increase in passive torque at end ROM) [26,27] and decrease in MTU stiffness [28].…”
Section: The Influence Of Chronic Stretching On Muscle Flexibility Anmentioning
confidence: 99%
“…Therefore, it becomes hard to consider sarcomerogenesis as a possible mechanism for increased performance following flexibility training. A recent investigation [31] reviewed six studies [26,28,[32][33][34][35] that evaluated the influence of static stretching training on isometric contractions. The authors observed that none of the included studies showed any improvement in performance after flexibility training using static stretching.…”
Section: The Influence Of Chronic Stretching On Muscle Flexibility Anmentioning
confidence: 99%
“…Peak torque is an absolute value (Kowalski, 2003). Static Stretch The technique of lengthening a muscle group by slowly moving a joint to its maximal range of motion and maintaining the position for a period of time (Guissard & Duchateau, 2004).…”
Section: Introductionmentioning
confidence: 99%